Saeed bin Al-Walid Al-Abrash Historical study (100-136 AH / 718 - 753 AD) (Journal of the College of Basic Education, 2024)
Our study deals with this topic entitled (Saeed bin Al-Walid Al-Abrash - a historical study for the period (100-136 AH / 718 - 753 AD) due to the importance of this topic in the study of Islamic history. However, in our study, we directed this discussion first to mention his name and lineage, who descends from the Kalb tribe, which is One of the Arab tribes that played an important role in political and military events, especially in Islamic history. Saeed bin Al-Walid was known by the nickname Al-Abrash, and it was said that the reason for this name was his Barsh. As for his predominant nickname (Abu Mujasha), Saeed bin Al-Walid Al-Abrash proved his ability and administrative competence. Through his assumption of the position of scribe, especially during the reign of Caliph Hisham bin Abdul Malik (100-125 AH / 718-742 AD(.Saeed bin Al-Walid was also one of the close writers of Hisham bin Abdul Malik, and this was confirmed by Al-Tabari (d. 310 AH) when he said, “If Hisham wanted something, Al-Abrash ordered it to happen.”